Moisture sorption isotherms cassava starch kaffir lime bioplastic films: article / Ahmad Faris Ahmad Azli, Junaidah Jai and Norasmah Mohammed Manshor - Ahmad ‘Azli, Ahmad Faris; Jai, Junaidah; Mohammed Manshor, Norasmah (2019)
Cassava starch can be used in the formation of biodegradable films and containers, as an alternative for polymer derived from petrol.”Kaffir lime oil act as antimicrobial agent that can inhibit the growth of bacteria in the food packaging.”Bioplastic films from cassava starch with 35 w/w glycerol were produced by casting method. The concentration of glycerol which is 35 w/w as a plasticizer.”Equilibrium moisture content at temperature 25oC and the water activity at range 0.05 to 0.9 by using static gravimetric method was determined.”Moisture sorption isotherms were measured through a standard saturated salt slurry method.”Five saturated salt solutions which are KOH, NaCI, BaCI2, KCI, NaNO3 were prepared corresponding to wide range of water activities.”The result of monolayer moisture contents of bioplastic films was evaluated using Brunauer Emmett and Telle (BET) sorption equation.”The isotherms exhibited Type III behaviour. Type III behaviour, in which a small amount of water was adsorbed in low water activity and the amount absorbed in larger water activity.”The moisture sorption data were fitted to BET models and a non-linear regression method was used to evaluate the value constant of the sorption equations.”The highest R2 values ranging between 0.9439 to 0.9850 and the value of MRPD values ranging between 9.1882 to 18.3558.”The monolayer, Mo value in this study was determined by using the BET equation and was obtained between range 0.0429-0.0469 gram water per gram dry matter following adsorption at 25oC.”The bioplastic film is suitable as packaging because the microorganism unable to grow below water activity of 0.91. There is no significant effect in moisture content with an increase of concentration of kaffir lime.